Cosmology with Gravitational Waves in DES and LSST. Issue Volume 13:Issue S338(2017) (29th January 2019) - Herner, Kenneth; Soares-Santos, Marcelle; Annis, James
Abstract: Motivated by the prospect of the wealth of data arising from the inauguration of the era of gravitational wave detection by ground-based interferometers the DES collaboration, in partnership with members of the LIGO collaboration and members of the astronomical community at large, have established a research program to search for their optical counterparts and to explore their use as cosmological probes. In this talk we present the status of our program and discuss prospects for establishing this new probe as part of the portfolio of the Dark Energy research program in the future, in particular for the next generation survey, LSST.